Quantitative and causal analysis for inflammatory genes and the risk of Parkinson’s disease - Yi, Minhan; Li, Jiaxin; Jian, Shijie; Li, Binbin; Huang, Zini; Shu, Li; Zhang, Yuan (Frontiers in Immunology, 2023)
Background The dysfunction of immune system and inflammation contribute to the Parkinson’s disease (PD) pathogenesis. Cytokines, oxidative stress, neurotoxin and metabolism associated enzymes participate in neuroinflammation in PD and the genes involved in them have been reported to be associated with the risk of PD. In our study, we performed a quantitative and causal analysis of the relationship between inflammatory genes and PD risk. Methods Standard process was performed for quantitative analysis. Allele model (AM) was used as primary outcome analysis and dominant model (DM) and recessive model (RM) were applied to do the secondary analysis. Then, for those genes significantly associated with the risk of PD, we used the published GWAS summary statistics for Mendelian Randomization (MR) to test the causal analysis between them. Results We included 36 variants in 18 genes for final pooled analysis. As a result, IL-6 rs1800795, TNF-α rs1799964, PON1 rs854560, CYP2D6 rs3892097, HLA-DRB rs660895, BST1 rs11931532, CCDC62 rs12817488 polymorphisms were associated with the risk of PD statistically with the ORs ranged from 0.66 to 3.19 while variants in IL-1α, IL-1β, IL-10, MnSOD, NFE2L2, CYP2E1, NOS1, NAT2, ABCB1, HFE and MTHFR were not related to the risk of PD. Besides, we observed that increasing ADP-ribosyl cyclase (coded by BST1) had causal effect on higher PD risk (OR[95%CI] =1.16[1.10-1.22]) while PON1(coded by PON1) shown probably protective effect on PD risk (OR[95%CI] =0.81[0.66-0.99]). Conclusion Several polymorphisms from inflammatory genes of IL-6, TNF-α, PON1, CYP2D6, HLA-DRB, BST1, CCDC62 were statistically associated with the susceptibility of PD, and with evidence of causal relationships for ADP-ribosyl cyclase and PON1 on PD risk, which may help understand the mechanisms and pathways underlying PD pathogenesis.